Penerapan PSAK 10 Tentang Penyajian Laporan Keuangan pada Transaksi Valuta Asing untuk Menunjang Kewajaran Laporan Keuangan PT JFI - Dhela Fajar Pratiwi; Endang Asliana; Nurmala Nurmala (Jurnal Ilmiah ESAI, 2021)
Foreign exchange transactions are transactions related to foreign currencies, where the exchange rate at any time will rapidly change in value, this is what often becomes a problem and causes foreign exchange differences. This writing aims to determine the accounting treatment of sales transactions, purchases related to PT JFI’s foreign exchange, and to find out the fairness of the financial statements. The secondary company data used by the author is PT JFI's 2019 financial report, data on changes in the closing exchange rate on December 31, 2019, a list of the total cash, receivables, and debts of USD and EURO in 2019. The results of this paper state that, the accounting treatment of foreign exchange differences in PT JFI's financial statements is not in accordance with PSAK 10, and the foreign exchange difference at PT JFI also causes the amount of profit in the financial statements not to show the actual situation, thus affecting audit income on the fairness of the financial statements.